Struktur und Variabilität des westlichen Randstromsystems im Subtropischen Nordatlantik: Analyse eines globalen Ozeanmodells (ORCA025) - Müller, Katharina (2010)
Many studies about the Western Boundary Currents in the subtropical North Atlantic,important components of the Meridional Overturning Circulation and the subtropical gyre, have been made during the last few decades. There is data from direct current measurements and more than 25 years of cable derived data. In this work the structure of the Western Boundary Currents and especially the variability of the Florida Current are examined with the help of a global ocean modell (ORCA025). The determined seasonal cycle is similar to the observed one. There are parallels between the cable data and the model-output on decadal timescales. Both show an increase in transport during the 1990s. The local windfield can be varified as the main cause of the seasonal cycle. However, such an influence seem to decrease on longer timescales. Substantial changes in the seasonal cycle can not be detected. On decadal timescales there may be a coherence between the NAO and the Florida Current transport, which can either be explained with the connection to the MOC, or maybe with the wind stress curl over the subtropical North Atlantic.